Asas Kepastian Hukum Terhadap Kewenangan Inpektorat Dalam Penyelenggaraan Pengawasan Pemerintah Daerah - Pandri Zulfikar (JUNCTO: Jurnal Ilmiah Hukum, 2022)
Constitutionally the Regional Government has the authority to regulate and manage its own Government Affairs, the Principles of Autonomy and Co-Administration are given the widest possible autonomy. The legal basis for the authority of district/city regional inspectors in Indonesia is in Law Number 23 of 2014 concerning Regional Government in conjunction with Government Regulation of the Republic of Indonesia Number 60 of 2008 concerning the Government's Internal Control System in conjunction with Government Regulation of the Republic of Indonesia Number 18 of 2016 concerning Regional Apparatuses in conjunction with Regulations Government of the Republic of Indonesia Number 12 of 2017 concerning Guidance and Supervision of the Implementation of Regional Government in conjunction with Presidential Regulation Number 54 of 2010 concerning Government Procurement of Goods/Services in conjunction with Minister of Home Affairs Regulation Number 64 of 2007 concerning Technical Guidelines for the Organization and Working Procedures of Provincial and Regency/City Inspectorates. Government Internal Supervisory Apparatus (APIP), the author conducts research, studies, and analyzes how the mechanisms for strengthening regional inspectorate institutions in supervising local governments and how are the mechanisms for strengthening regional inspectorate institutions in carrying out supervision on regional governments. Types of normative legal research related to laws and regulations, are descriptive in nature, namely describing the symptoms that exist in the community towards those being studied. A qualitative approach produces descriptive data with the aim of understanding the symptoms studied. Normative legal research, namely: Primary legal material is what binds people to comply with laws and regulations, and judge's decisions. Secondary legal materials explain primary legal materials. Tertiary Legal Materials supports primary legal materials and secondary legal materials, namely the Big Indonesian Dictionary and the black's law dictionary. Theoretical study is the Principle of Legal Certainty is a justifiable protection against arbitrary actions, which means that someone will be able to obtain something that is expected in certain circumstances (Soedikno Mertokusumo. 1999). The research results of researchers, supervisory duties, mechanisms, structural positions that are appointed and dismissed, are under and are responsible for the regional head of the Regent/Mayor. strengthening the independence of tasks and supervisory authority, so that they can run effectively, namely they are no longer responsible to the Regent/Mayor but at a higher level/equivalent to the regional secretary to become echelon II/a.